KDM5A, a H3K4me3 demethylase, regulates skin wound healing by promoting M2 macrophage polarization via suppression of Socs1 - Zhang, Jixun; Wang, Chao; Dong, Xinxin (Frontiers in Physiology, 2025)
IntroductionThe inflammatory phase is critical for successful wound healing, with macrophages playing a central role by polarizing into different functional phenotypes. KDM5A, a histone demethylase, can epigenetically suppress Socs1, a key negative regulator of immune responses. However, the specific roles and mechanisms of the KDM5A-Socs1 axis in macrophage polarization during cutaneous wound healing remain largely unknown. This study aims to elucidate the function of KDM5A in wound repair, focusing on its regulatory crosstalk with Socs1 in macrophages.MethodsWe established a murine wound model to systematically evaluate wound closure kinetics, collagen deposition, healing scores, macrophage polarization dynamics, and inflammatory cytokine profiles. An in vitro co-culture system of macrophages and fibroblasts under KDM5A perturbation was used to assess its impact on fibroblast proliferation, migration, and angiogenic capacity. Mechanistic insights were gained through chromatin immunoprecipitation (ChIP) assays to determine the epigenetic regulation of Socs1 by KDM5A.ResultsKDM5A expression was significantly downregulated in wound-associated macrophages and was inversely correlated with M2 polarization. Genetic ablation of KDM5A accelerated cutaneous wound closure, enhanced collagen deposition, and improved healing scores. Mechanistically, KDM5A deficiency elevated the activating histone marks H3K4me3 and H3K27ac at the Socs1 promoter, augmenting its transcriptional activation. The subsequent upregulation of Socs1 promoted M2 macrophage polarization, attenuated pro-inflammatory cytokine secretion, and stimulated fibroblast proliferation, migration, and angiogenesis.DiscussionOur findings demonstrate that KDM5A modulates wound healing by epigenetically regulating Socs1 expression. Downregulation of KDM5A in wound macrophages relieves the repression of Socs1, thereby driving M2 polarization and creating a pro-regenerative microenvironment that facilitates tissue repair. This study elucidates the KDM5A-Socs1 molecular axis as a key epigenetic regulator in wound healing and establishes a conceptual framework for developing novel therapeutic strategies.